Estimating Power Pump Loads and Sizing Generators for Ship Electrical Load Analysis - Chin, Hai-Ming; Su, Chun-Lien; Liao, Chi-Hsiang (IEEE transactions on industry applications, 2016)
One of the most basic tasks for ship power system design is electrical load analysis, which is used to determine the required installed capacity of on-board power generators. Traditionally, the analysis is carried out based on considerations of investment cost and supply adequacy, while using a design of generators with the same rating. It does not consider the energy efficiency, thereby in some cases resulting in the generators operated at a lower efficiency under heavy loading conditions and high energy consumption. To enhance power generation efficiency and reduce energy cost, a new load analysis method for marine vessels is proposed in this paper. The relationship of operating efficiency and load factor of generators is mathematically modeled and considered in the analysis. The problem is formulated as a nondifferential combinational optimization problem, where the total generation cost during a whole voyage is minimized subject to system operation and technical constraints, in order to derive the optimal generator rated power and unit commitment using genetic algorithms. The results confirmed the validity of the proposed method through load analysis of a practical ship power system, as well as energy-saving benefits using the proper generator rated power and an accurate load model for power pumps.